Розробка компонентів crm-системи для автоматизації менеджменту медичних послуг - Коновалова, М. Д. (ХНУРЕ, 2024)
The report considers the stages of designing and creating a CRM system for the automation of medical services management by e-mail newsletter. ActiveCampaign software as a service (SaaS) was used to track the customer's step-by-step actions. It provides companies with personalization and automation capabilities to attract high-quality customers, increase customer engagement, and combine data to improve the effectiveness of marketing efforts – all within a centralized platform.
Keywords: інтерфейс користувача; база даних пацієнтів; система запису; управління медичними записами